Reindustrialization, Innovative Sustainable Economic Development, and Societal Values: A Cluster Analysis Approach - Elena Maslyukova; Vyacheslav Volchik; Wadim Strielkowski (Economies)
Our paper explores the challenges of industrial development by examining two contrasting theoretical frameworks: (i) the mainstream economic approach which emphasizes capital accumulation, innovation, and profit maximization within a globalized context, and (ii) the classical institutional economics perspective, rooted in the so-called “Veblen Dichotomy”. The latter contrasts monetary institutions focused on short-term profits with those centered on organizational, social, environmental, and business values that foster long-term technological progress. We analyze reindustrialization processes and assess the hypothesis that the conflict between these divergent institutions and social values plays a critical role in creating an institutional environment conducive to innovation and economic development. Our research highlights how technological advancements contribute to the physical and geographical fragmentation of industrial activities, thereby driving the spatial restructuring of economies. Furthermore, this paper addresses the growing prominence of intangible production, noting how deindustrialization, driven by shifts toward service-based economies, is closely related to the broader processes of globalization. The paper employs cluster analysis to explore the links between reindustrialization, institutional dynamics, and societal values across four groups (clusters) of countries. Our results reveal differences and similarities between these groups of countries and offer policy implications and suggestions for improvements. These results might be of special interest for relevant stakeholders and policymakers, as well as for researchers focused on innovative industrial and economic development.